The Scientific Miracles of the Prophet's Hadiths and the Rules of Its Application | قضية الإعجاز العلمي للأحاديث النبوية وضوابط التعامل معها - Ade Supriyadi (Al-Zahra : Journal for Islamic and Arabic Studies, 2018)
Preparing the preacher and Imam of the mosque with special qualification is supposed to be an important duty. Because promoting to perform worship to Allah and guiding people in the right way is an honourable work. The process of promoting, furthermore, should be in accordance with the path Prophet PBUH paved in. This article demonstrates the reason why preacher and Imam should have good qualifications and competencies and what fields they should be experts on those. In addition, the writer viewed that preacher and Imam have to meet the requirement of a number of knowledge in Islam and skills of leadership as they will live in society and solve their problems.